O cronică rimată a perioadei interbelice: Jean Moscopol, 101 „răutăți” epigramatice - Alexandra Oprescu (Revista de Istorie și Teorie Literară)
In this paper I intend to offer an adequate interpretation of the volume published by Jean Moscopol, 101 “Sharp” Epigrams, using a faithfull reconstruction of the interwar’s cultural context. It may seem curious that, when writing about a famous diseur, I quote diary pages that do not belong to the subject of this research, newspapers clippings, or even scenes taken from the Eastern European novel. All in order to recreate, as faithfully as possible, the portraits of the addresses. These epigrams are not subjected to an aesthetic judgement, although I’m pretty sure that Literature was lying beneath all the sarcasm, for neither the sense of language, nor the pleasure in observing people he missed. However, the small linguistic acrobatics, the naturalness and even the naivety of his verse are also worth noting. Finally, given the subjective nature of writing, of course we cannot attribute a certain historical value to Moscopol’s volume. Though, I do think that we may see it as one large vintage group picture. My main mission? That of restoring this faded, quite unknown picture.